Influence of Discipline and Pedagogical Competence on the Performance of Arabic Language Teachers / Pengaruh Disiplin Dan Kompetensi Pedagogis Terhadap Kinerja Guru Bahasa Arab - Eka Putri Zulfatussoraya; Umi Hijriyah; Koderi Koderi; Muhammad Sufian; Erlina Erlina (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2023)
This study investigates the impact of discipline and pedagogical competence on the performance of Arabic language teachers at Natar Integrated Islamic School in South Lampung. Drawing upon a mixed-methods approach, the research delves into the correlation between teachers' disciplinary practices and their pedagogical competencies in the context of an integrated Islamic educational setting. Quantitative data was gathered through surveys, while qualitative insights were obtained via interviews and classroom observations. The findings reveal a significant interplay between teachers' disciplinary commitment and their pedagogical skills, underscoring the pivotal role of both factors in shaping effective Arabic language instruction. The study not only sheds light on the complex dynamics of these elements but also offers practical implications for enhancing teacher performance in Islamic educational institutions. This research contributes to the broader discourse on teacher development and educational quality within the specific cultural and pedagogical nuances of integrated Islamic schools.Abstrak: Penelitian ini menyelidiki pengaruh disiplin dan kompetensi pedagogis terhadap kinerja guru bahasa Arab di Sekolah Islam Terpadu Natar di Lampung Selatan. Dengan menggunakan pendekatan campuran, penelitian ini menggali hubungan antara praktik disiplin guru dan kompetensi pedagogis mereka dalam konteks pendidikan Islam terpadu. Data kuantitatif dikumpulkan melalui survei, sementara wawasan kualitatif diperoleh melalui wawancara dan observasi kelas. Temuan penelitian ini mengungkapkan adanya interaksi signifikan antara komitmen disiplin guru dan keterampilan pedagogis mereka, yang menekankan peran penting kedua faktor ini dalam membentuk instruksi bahasa Arab yang efektif. Penelitian ini tidak hanya memberikan pemahaman tentang dinamika kompleks dari elemen-elemen ini, tetapi juga menawarkan implikasi praktis untuk meningkatkan kinerja guru di institusi pendidikan Islam. Penelitian ini berkontribusi pada wacana lebih luas tentang pengembangan guru dan kualitas pendidikan dalam nuansa budaya dan pedagogi khusus sekolah Islam terpadu.This study investigates the impact of discipline and pedagogical competence on the performance of Arabic language teachers at Natar Integrated Islamic School in South Lampung. Drawing upon a mixed-methods approach, the research delves into the correlation between teachers' disciplinary practices and their pedagogical competencies in the context of an integrated Islamic educational setting. Quantitative data was gathered through surveys, while qualitative insights were obtained via interviews and classroom observations. The findings of this research reveal that there is a significant influence between teacher discipline and their pedagogical abilities on the performance of Arabic Language Teachers in establishing effective Arabic language learning. This research provides an understanding of the complex dynamics of the elements of Arabic teacher performance, and also offers practical implications for improving teacher performance in Islamic educational institutions. This research contributes to teacher development and educational quality in discipline, pedagogy and teacher performance in integrated Islamic schools. Abstrak: Penelitian ini menyelidiki pengaruh disiplin dan kompetensi pedagogis terhadap kinerja guru bahasa Arab di Sekolah Islam Terpadu Natar di Lampung Selatan. Dengan menggunakan pendekatan campuran, penelitian ini menggali hubungan antara praktik disiplin guru dan kompetensi pedagogis mereka dalam konteks pendidikan Islam terpadu. Data kuantitatif dikumpulkan melalui survei, sementara wawasan kualitatif diperoleh melalui wawancara dan observasi kelas. Temuan penelitian ini mengungkapkan adanya pengaruh signifikan antara kedisiplinan guru dan kemampuan pedagogis mereka, terhadap kinerja Guru Bahasa Arab dalam membentuk pemebeajaran bahasa Arab yang efektif. Penelitian ini memberikan pemahaman tentang dinamika kompleks dari elemen-elemen kinerja Guru Bahasa Arab, juga menawarkan implikasi praktis untuk meningkatkan kinerja guru di institusi pendidikan Islam. Penelitian ini berkontribusi dalam pengembangan guru dan kualitas pendidikan dalam kedisiplinan, pedagogi dan kinerja Guru dalam sekolah Islam terpadu.